Microbiological and chemical characterization of water kefir: An innovative source of potential probiotics for bee nutrition - Rodríguez, María A. (2023)
We evaluated the microbial composition of water kefir grains and beverage over the course of one year to determine whether the number and type of microorganisms changed over the time. Bacteria and yeast colonies with different morphologies were isolated from water kefir and their antimicrobial activity was evaluated against Paenibacillus larvae and Ascosphaera apis. A chemical characterization of kefir was also carried out. Our results confirmed that bacteria and yeasts were more numerous in kefir grains compared with those in the beverage. The counts of microorganisms declined, although an important microbial community was still present in kefir after the long storage period. Eleven strains which inhibited bee pathogens were isolated from kefir. Genotypic results demonstrated that these isolates included Lentilactobacillus hilgardii, Lentilactobacillus buchneri and Saccharomyces cerevisiae. Thus, water kefir may be an innovative source of potential probiotic strains for bee nutrition in order to control honeybee diseases.